Evaluation of Human IgM and IgG Titers in Iraq Following Vaccination with the mRNA and the Inactivated COVID-19 Vaccine at One Month and Six Months (Tikrit Journal of Veterinary Science, 2023)
After the outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) in 2019, many types of vaccines have been designed and some are approved by the World Health Organization (WHO). This study conducted to measure the efficacy of tow type of vaccines, the mRNA vaccine and inactivated vaccine, by detecting the concentration of IgM and IgG in serum of human after one month and six months of vaccination with the two types of the vaccine mentioned above. Concentrations of IgM and IgG in serum of participants were measured using a VIDAS device (bioMérieux, France) and following the manufacturer's instructions. The results showed that IgM concentrations decreased to below the protective level in both types of vaccine after one or six months of vaccination, and there were no significant differences (p ˃ 0.05) between the two types of vaccine. However, after one month of vaccination, there was a significant difference (p ≤ 0.05) in the IgG concentration in the serum of the mRNA vaccine group (32.7898 BAU/mL), and the inactivated vaccine group (8.17 BAU/mL). Likewise, after six months there was a significant difference (p ≤ 0.05) in the IgG concentration in the serum of the mRNA vaccine group (27.03 BAU/mL) and the inactivated vaccine group (6.91 BAU/mL). The mRNA vaccine is more efficient than the inactivated type as the IgG concentration remain higher and it lasts more time.